Analisis Wacana terhadap Teks Argumentatif Persuasif dalam Video Iklan Investasi Ternak Uang dan Bibit: Discourse Analysis of Argumentative Persuasive Text in Investment Advertisement Video of Ternak Uang and Bibit - Harsa Alim (TOTOBUANG, 2022)
Advertisement is a media or way for people to promote something or services in form text, audio, visual, or even audio visual. In discourse analysis, we do not only focus on the written text but also oral text. Advertisement can be categorized as an argumentative and persuasive discourse. The objective of this paper is to analyze the discourse in Ternak Uang and Bibit. The advertisement itself is in the form of audio visual or video on Youtube as their platform of advertising. This research used Stephen Toulmin’s model approach to analyze the argumentative and persuasive elements in Ternak Uang and Bibit advertisement after made a transcription beforehand. Besides, this research also used Laswell communication approach to analyze the communication elements of psychosocial factors in that advertisement. The result shows that there are argumentative and persuasive elements of claim, data, warrant, backing, but not with rebuttal that are connected with how they persuade people to use their product and service. The communication elements of who, what, which channel, to whom and for what impact also shows that the discourse that are brought to the audience is on point and in line with the target that want to be achieved by the company. Keywords: advertisement, argumentative, persuasive